SUKUK TABUNGAN SEBAGAI RETURN ASET BEBAS RISIKO PADA MODEL INDEKS TUNGGAL DALAM PEMBENTUKAN PORTOFOLIO OPTIMAL SAHAM JAKARTA ISLAMIC INDEX - Sri Istiyarti Uswatun Chasanah (Math Program, Math and Science faculty, Pamulang University, 2023)
Sukuk (sharia bonds) are a profitable investment because they can provide higher returns compared to deposits. In addition, sukuk can also make investors feel safe with very low risk, and can even be considered a risk-free rate. This study uses the value of savings sukuk as a risk-free ratet (R_f) which is used to form a stock portfolio with the Single Index Model. The stocks used in this study are stocks that are included in the Jakarta Islamic Index (JII) for three periods. Based on data on the research range, namely June 1 2020-May 31 2021, a combination of stock proportions in the formation of an optimal portfolio is obtained using the Single Index Model as follows ANTM 38%, JPFA 31%, UNTR 23%, INCO 4% and TKIM 3%. From these proportions, a profit of 0.0188 and a risk of 0.0729 are obtained every week.